Local Delivery of Therapeutics to the Inner Ear: The State of the Science - Anderson, Caroline R.; Xie, Carol; Su, Matthew P.; Garcia, Maria; Blackshaw, Helen; Schilder, Anne G. M. (Frontiers in Cellular Neuroscience, 2019)
Background Advances in the understanding of the genetic and molecular aetiologies of inner ear disorders have enabled the identification of therapeutic targets and innovative delivery approaches to the inner ear. As this field grows, the need for knowledge about effective delivery of therapeutics to the inner ear has become a priority. This review maps all clinical and pre-clinical research published in English in the field to date, to guide both researchers and clinicians about local drug delivery methods in the context of novel therapeutics. Methods A systematic search was conducted using customised strategies in Cochrane, Pubmed, EMBASE databases from inception to the 30/09/2018. Two researchers undertook study selection and data extraction independently. Results Our search returned 12,200 articles, of which 837 articles met the inclusion criteria. 679 were original research and 158 were reviews. There has been a steady increase in the numbers of publications related to inner ear therapeutics delivery over the last three decades, with a sharp rise over the last two years. The intra-tympanic route accounts for over 70% of published articles. Less than one third of published research directly assesses delivery efficacy, with most papers using clinical efficacy as a surrogate marker. Conclusion Research into local therapeutic delivery to the inner ear has undergone a recent surge, improving our understanding of how novel therapeutics can be delivered. Direct assessment of delivery efficacy is challenging, especially in humans, and progress in this area is key to understanding how to make decisions about delivery of novel hearing therapeutics.